2017
DOI: 10.1177/1046878117738552
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Developing Motor Skills Through Motion-Based Video Gaming: A Review

Abstract: Background. Technology growth affords innovative teaching techniques as video gaming within education has increased in popularity. Motion-based video gaming (MBVG) is a type of gaming that requires the individual playing the game to be physically interactive. Thus, whatever movements the individual playing the game does is picked up by motion sensors and is mimicked via the on-screen character. MBVG provides constant feedback to learners and has been found to help motivate students, replace sedentary with acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
(40 reference statements)
0
16
0
3
Order By: Relevance
“…An innovative learning model is needed to meet the requirements of a future career and helps to build a dynamic, high-quality educational system (Zhang, 2019). Many authors emphasize the importance of information multimedia and virtual reality technologies for teaching various sports and physical training (Jenny et al, 2017;Yang, 2018). The positive effect of their use for teaching students is emphasized (Lubis et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An innovative learning model is needed to meet the requirements of a future career and helps to build a dynamic, high-quality educational system (Zhang, 2019). Many authors emphasize the importance of information multimedia and virtual reality technologies for teaching various sports and physical training (Jenny et al, 2017;Yang, 2018). The positive effect of their use for teaching students is emphasized (Lubis et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, within the last decade, with the field of e-sports another interesting area of application has emerged. Since 2006, when Nintendo released its Wii console, motion-controlled gaming systems have evolved so much that they are now used for therapeutic [7] and educational purposes [8]. Today, there are two application methods when dealing with human motion recognition: the vision-or video-based approach and the use of wearable sensor technology worn by the user.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic analysis of the literature by Jenny et al . () reveals that only a small number of studies found commercial exergameplay to have a positive effect on FMS performance. Furthermore, studies that show positive findings typically refer to balance and/or object control skills (kick, catch, throw, etc).…”
Section: Introductionmentioning
confidence: 98%